Implementasi Pembelajaran Pendidikan Agama Islam (PAI) Berbasis Luring dan Daring Pada Masa Pandemi - Febi Khumairoh; Abdul Kadir (Jurnal Alasma : Media Informasi dan Komunikasi Ilmiah, 2022)
This paper comes from the results of research that discusses the implementation of offline and online-based Islamic Religious Education learning during the pandemic. The objectives of this study are: 1) To find out how to implement offline learning during the Covid-19 period. 2) To find out the shortcomings and advantages in the implementation of offline learning during the Covid-19 pandemic at the Asian-African Muslim Junior High School, South Tangerang City, Banten. This research is a qualitative research with descriptive analysis techniques. Data analysis of research results is obtained from the process of systematically searching and compiling, data obtained from the results of observation, interviews and documentation, namely data collection, data reduction, data presentation, conclusions and verification. In the observation activities of researchers as non-participant-observers, interviews were conducted to extract information from principals, vice principals, teachers and student representatives. The results showed that, 1) The implementation of the offline learning model in Asian African Muslim Junior High Schools is the same as usual learning, but learning is carried out with an odd-even system and is divided into 2 groups in 1 class. 2) Shortcomings in the implementation of offline learning, namely, limited time, lack of orderly implementation of health protocols. The advantages of the offline learning model are that students understand the lessons delivered by the teacher faster, students are more enthusiastic in participating in teaching and learning activities.